2013
DOI: 10.1002/jcp.24312
|View full text |Cite
|
Sign up to set email alerts
|

An integrated understanding of the physiological response to elevated extracellular phosphate

Abstract: Recent studies have suggested that changes in serum phosphate levels influence pathological states associated with aging such as cancer, bone metabolism, and cardiovascular function, even in individuals with normal renal function. The causes are only beginning to be elucidated but are likely a combination of endocrine, paracrine, autocrine, and cell autonomous effects. We have used an integrated quantitative biology approach, combining transcriptomics and proteomics to define a multi-phase, extracellular phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 118 publications
12
97
0
Order By: Relevance
“…Previous work has indicated that P i levels influence ATP production (30). Indeed, we found that our P i starvation protocol reduced [ATP] by 66% (Fig.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Previous work has indicated that P i levels influence ATP production (30). Indeed, we found that our P i starvation protocol reduced [ATP] by 66% (Fig.…”
Section: Resultssupporting
confidence: 57%
“…8 Accumulation-Our main experimental paradigm has been to impose a nutritional challenge upon cultured cells: deprive and then restore the levels of P i found in serum. Other groups have studied the impact upon signal transduction cascades when cells are incubated with "high" [P i ] (5-10 mM) (2,30). We noted that such dramatic fluctuations in extracellular P i concentration (up to 10 mM or more) are physiologically relevant for cells that line the gastrointestinal tract (12).…”
Section: Kinetic Analysis Of the Bifunctional Human Ppip5ks: The Intementioning
confidence: 87%
See 2 more Smart Citations
“…In addition to the widespread structural and metabolic functions of Pi, it has become increasingly apparent during the past 15 years that extracellular Pi can act as a signaling molecule directly altering gene expression and cell phenotype (6)(7)(8)(9). The abundance of Pi in the skeleton has led to early studies describing the effects of extracellular Pi in this organ.…”
mentioning
confidence: 99%